Biomass derived activated carbon catalysts for the one-step dimethyl ether synthesis from syngas - Palomo-Jiménez, José; Rodríguez-Cano, Miguel Ángel; Rodríguez-Mirasol, José; Cordero-Alcántara, Tomás (My University, 2019)
In this work we study the behaviour of a carbon-based catalyst for this one-step synthesis process. Two kinds of activated carbons, prepared by chemical (with H3PO4) and physical (by CO2 partial gasification) activation of olive stones, were used as catalysts support. The main difference between the activated carbons was the presence of chemically stable phosphorus surface groups, mainly in form of C-O-PO3 groups1, on the activated carbon prepared via chemical activation. The addition of Zr to the chemically activated carbon (ACPZr) resulted in the formation of zirconium phosphate species on the carbon surface, which were capable of promoting the selective methanol dehydration to DME. Cu-Zn loading on the chemically activated carbon resulted in strong interactions between the metallic phase and the phosphate surface groups due to the formation Cu phosphate species. The bifunctional catalyst, ACPZrCuZn showed less conversion that the physical mixture. This fact is related with the presence of phosphorus species that avoids the reduction of the metal (copper).
Se trata de un resumen extendido de una comunicación a congreso internacional.
Keywords: Catalizadores; Carbono; Dimethyl ether; Carbon catalyst; Biomass; Nanoporous materials; Acid